RANCANG BANGUN SISTEM MONITORING DAN KONTROL PENGGUNAAN AIR PDAM BERBASIS INTERNET OF THINGS - Julian Anggara; Nehru Nehru; Yosi Riduas Hais (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2023)
The water usage recording system for PDAM customers still uses a manual data collection system by officers. The problem is that officers do not carry out routine records but only estimate water usage based on previous month's usage. This results in swelling when recording after several months of use. The aim of this research is to 1) design an IoT-based PDAM water use monitoring and control system tool and 2) analyze the performance of the PDAM water use monitoring and control tool. An IoT-based PDAM water usage monitoring and control tool equipped with a YF-S201 water flow sensor to read how much water is flowing. This tool is also equipped with a solenoid valve which functions as a tap to turn the water on and off and NTP (network time protocol) which is used as a timer. The testing is carried out to determine the overall performance of the tool such as waterflow sensor performance, web application performance and communication between the controller and the web application. The test results of the YF-S201 water flow sensor can read water flow with an average error of 0.78%. This sensor can work well in reading water flow because the greater the water flow that passes through it, the smaller the error value will be. The selenoid valve can also run smoothly when the website gives a command to turn the valve on or off. The website can display the values ​​produced by the water flow sensor precisely and accurately.